PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI DAN PELATIHAN PEMBUATAN KOMBUCHA SEBAGAI MINUMAN YANG MENINGKATKAN IMUNITAS TUBUH DAN PENCERNAAN - Sukawaty, Yullia; Rachman, Rika Didi; Afifah R, Enci Nurul; Fadillah, Dwi Hurulaini; Fitriani, Eka Nurul; Natalya Putri, Rezky; Fuadah, Windy Samrotul; Yusdiansah , Rian (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
The community service activity entitled “Empowering the Community Through Education and Training in Kombucha Production as a Beverage that Boosts Immunity and Digestion” aims to improve the knowledge and skills of residents of Tani Aman Village RT 23 in processing kombucha as a fermented beverage that is beneficial to health. Kombucha is known to contain antioxidants, probiotics, and bioactive compounds that are good for immune system strength and digestion. Unfortunately, its utilization remains low due to a lack of information and technical skills among the community. This initiative was carried out through interactive education and training workshops, which not only provided theoretical knowledge but also hands-on practice. The results demonstrated an increase in residents' understanding and interest in making kombucha independently. In addition to its positive impact on health, this activity also served as a valuable experience in fostering relationships and collaboration between the implementing team and the community